2007
DOI: 10.1007/s11434-007-0477-5
|View full text |Cite
|
Sign up to set email alerts
|

Enolate chelating N-heterocyclic carbene complexes of Fe(II): Synthesis, structure and their catalytic activity for ring-opening polymerization of ɛ-caprolactone

Abstract: respectively. Attempt to synthesize mono-ligand Fe(II) bromide by the 1:1 molar ratio of NaL to FeBr 2 is unsuccessful, and the same complexes of 3 and 4 were obtained. Both 3 and 4 have been depicted by elemental analysis and X-ray structure determination. Preliminary studies show that both 3 and 4 can be used as single-component catalyst for the ring-opening polymerization of ε-caprolactone, and the catalytic activity of 3 is higher than that of 4. iron complex, functionalized N-heterocyclic carbene, ε-capro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Due to intramolecular transesterification reactions, the control of the chain length and the polydispersity was low during the polymerization. New Fe‐NHC complexes chelated by an enolate moiety ( C7 and C8 , Figure 4) gave similar results in ε‐caprolactone polymerization 19…”
Section: Polymerization Reactionsmentioning
confidence: 67%
“…Due to intramolecular transesterification reactions, the control of the chain length and the polydispersity was low during the polymerization. New Fe‐NHC complexes chelated by an enolate moiety ( C7 and C8 , Figure 4) gave similar results in ε‐caprolactone polymerization 19…”
Section: Polymerization Reactionsmentioning
confidence: 67%
“…841 One of the complexes provided the polyester with a number-average molecular weight of 4.0 Â 10 4 in 100% yield after 9 h reaction time in toluene at 80°C. The molecular weight distribution of 3.1 was rather high indicating that inter-or intramolecular transesterification reactions may occur.…”
Section: Scheme 451mentioning
confidence: 99%
“…31 These were deprotonated and reacted with FeBr2 to give the five iron(II) complexes 1a-c and 2a, b, respectively (Scheme 2). 32,33 It is worth noting at this point, that even with ligand synthesis, these iron catalysts were prepared in 2steps and at considerably less cost than even commercially available Wilkinson's catalyst. 34 Single-crystal X-ray analysis revealed that these bis-ligated complexes all adopted a similar distorted tetrahedral structure featuring an anchoring iron-carbene bond and the potentially activating group in the Fe-O motif (see ESI for details).…”
Section: Take Down Policymentioning
confidence: 99%
“…31 These were deprotonated and reacted with FeBr 2 to give the five iron(II) complexes 1a−c and 2a,b, respectively (Scheme 2). 32,33 It is worth noting at this point, that even with ligand synthesis, these iron catalysts were prepared in 2-steps and at considerably less cost than even commercially available Wilkinson's catalyst. 34 Initial investigations into alkene hydroboration found success using catecholborane (HBcat).…”
mentioning
confidence: 99%